Dangerous intimacy : the untold story of Mark Twain's final years - Lystra, Karen (University of California Press, 2004)
The last phase of Mark Twain's life is sadly familiar: Crippled by losses and tragedies, America's greatest humorist sank into a deep and bitter depression. It is also wrong. This book recovers Twain's final years as they really were--lived in the shadow of deception and prejudice, but also in the light of the author's unflagging energy and enthusiasm.